WO3-Doped TiO2 Coating on Charcoal Activated with Increase Photocatalytic and Antibacterial Properties Synthesized by Microwave-Assisted Sol-Gel Method - Weerachai Sangchay (Journal of Nanotechnology)
WO3-doped TiO2 coating on charcoal activated (CA) was prepared by microwave-assisted sol-gel method. The samples calcined at the temperature of 500°C for 2 h with a heating rate of 10°C/min were characterized by XRD, EDS, and SEM. The photocatalytic and antibacterial activities of WO3-doped TiO2 coating on CA were investigated by means of degradation of a methylene blue (MB) solution and against the bacteria E. coli, respectively. The effects of WO3 concentration were discussed. The 1% WO3-doped TiO2 coated CA seems to exhibit the higher photocatalytic and antibacterial activity than other samples. The WO3-doped TiO2 coated on CA are expected to be applied as a photocatalyst for water purification.